Assessing and measuring the fiscal health of local governments: focus on Chicago suburban municipalities - Hendrick, Rebecca (2004)
This study presents a framework for assessing the financial condition and fiscal health of municipal governments, develops indices for some dimensions of the framework, and applies the indices to 264 suburban municipalities in the Chicago metropolitan region. The framework is based on a systems view of local government financial condition. It shows that fiscal health is a complex and multidimensional concept with varying time frames. Furthermore, the dimensions are related but often in indirect or nonlinear ways, indicating they must be measured separately rather than combined into a comprehensive indicator of fiscal health. Indices developed here for targeted dimensions of the framework are assessed and compared to alternative indicators of fiscal health developed by others in the field. - Reproduced.
Keywords: Public finance; Local finance; Local government